The Development of an Administrative Model for Students Qualities in Catholic Standard by Participatory Action Research: Case Study of Darasamutr School - Suksamran, Nantapon; Thongpang, Thanawin (Saengtham College Journal, 2025)
The purposes of this research aim 1) To study the management styles and conditions in Catholic schools under the Diocese of Chanthaburi; 2) To develop a quality management model for learners align to standard of Catholic education in basic education; 3) To study the effect of the use of the management model on the quality of learners according to the educational standards of Catholic primary education. This study is divided into 5 phases. Phase 1 analyzing and synthesizing information. Phase 2 to create a quality management model for learners in accordance with Catholic Education Standards through participatory action research. Phase 3 to develop a Quality Management Model for Learners Based on Catholic Education Standards. Phase 4 examine the suitability and performance of the model with quasi-experimental research and Phase 5 conclusion and endorsement of quality management models for learners in accordance with Catholic Education Standards. The participants included 45 administrators, teachers, students, and parents. The instrument used in the research were the questionnaire on the management model, a participatory note recording, field recording, quality assessment model for learners according to Catholic education standards, and qualitative and quantitative data analysis by descriptive statistics, ie mean and standard deviation. Qualitative analysis with content analysis The research findings that: 1. Management Patterns and Conditions in Catholic Schools under the Diocese of Chanthaburi by the educational standards of Catholic education with the vision of “Outstanding educational identity is a Catholic school of Catholic Education” the overall and category separately reported that the result was at the highest level and ranked from highest to lowest. The first three rank were administrators, management and the learning environment and the atmosphere of evangelized. And the last rank were the education for community. For an awareness of teachers’ duties in Catholic schools under the Diocese of Chanthaburi. According to the educational standards of Catholic education. The overall level was high level. 2. Quality management model for learners according to Catholic education standards. Responsibility The volunteer spirit Forgiveness And the nature of knowledge is the project is the teacher of life with the students by the Department of Administration together with the Department of Finance, the project coordinated by the curriculum management and academic work with the Department of moral ethics. The magic star project (Clean and Environmental Campaign) by Student Services and Activities. Volunteer activities developed by pastoral and apostolic ministry. Ethics and moral education by the Department of moral ethics. Moral activities lead the life of the pastoral and apostolic ministry in collaboration with the ethics and moral education department. And the Good Samaritan Sea Life Club. (Book of Good Deeds) by the Department of moral ethics together with the pastoral and apostolic department. 3. The effect of administrative model on quality of learners on Catholic education standards. The responsibility domain, the volunteer spirit domain, the forgiveness domain and the nature of caring domain were specified with all these 25 key point. 21 of these key points achieve the goal. 1 successful key point with the equally successful requiry and three successful key points were lower than expectation. Teachers who have participated in the project The teacher’s role considered as the life partner of the students had developed their own self-awareness to be lifelong companions higher than the previous patterns usage. The Matthayom 4 students participating in the experimental group using the quality administrative model of learners according to the Catholic Education Standards have changed their behavior in term of the responsibility domain, the volunteer spirit domain, the forgiveness domain and the nature of caring domain in the better than before using the administration model to qualify learners according to Catholic education standards.